COVID-19 Effects on Postgraduate Students’ Activity-Travel Patterns in UTHM - WAN AHMAD FATHIJAYA NINGRAT, WAN SITI NOR FARHANI; AHMAD TERMIDA, NURSITIHAZLIN (Recent Trends in Civil Engineering and Built Environment, 2022)
COVID-19 pandemic is the most impactful issue that all people in the world struggling with. The first case was detected in Wuhan, China in December 2019 and the virus spread rapidly around the world. Thus, the Malaysian government has applied some measures to control the spread of COVID-19 which is called Movement Control Order (MCO), Conditional Movement Control Order (CMCO), and Recovery Movement Control Order (RMCO). In each of the orders, there are a few new regulations that all Malaysians need to obey. Due to that, the activity-travel patterns of Malaysians including university students may be impacted. This study aims to analyzed students’ activity-travel patterns during COVID-19 pandemic situations. A total of 327 respondents were selected among postgraduate students in Universiti Tun Hussein Onn Malaysia (UTHM). The survey method via questionnaire instrument was applied in a form of Google Form. The questionnaire was distributed using various online platforms such as WhatsApp, Facebook, and Instagram. A quantitative method was applied in which that the students’ activity-travel patterns during COVID-19 are analyzed and performed in percentage form using Statistical Packages for Social Science (SPSS) Version 23 to analyze the data. Results show that the respondents prefer to use a car over other modes for participating in all activities. For trip frequency, the highest percentage (58.4%) is 1-2 trips made per day in weekends to do leisure activities. As for travel distance, respondents tend to travel between 6 to 20 km per day to participate in mandatory and maintenance activities on weekdays.